Pulmonary hypertension in adults with congenital heart disease: updated recommendations from the Cologne Consensus Conference 2018 - Kaemmerer, Harald; Apitz, Christian; Brockmeier, Konrad; Eicken, Andreas; Gorenflo, Matthias; Hager, Alfred; de Haan, Fokko; Huntgeburth, Michael; Kozlik-Feldmann, Rainer G.; Miera, Oliver; Diller, Gerhard P. (International journal of cardiology, 2018)
In the summer of 2016, delegates from the German Respiratory Society (DGP), the German Society of Cardiology (DGK) and the German Society of Pediatric Cardiology (DGPK) met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary hypertension (PH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines, aiming at their practical implementation, considering country-specific issues, and including new evidence, where available. To this end, a number of working groups was initiated, one of which was specifically dedicated to PH in adults associated with congenital heart disease (CHD). As such patients are often complex and require special attention, and the general PAH treatment algorithm in the ESC/ERS guidelines appears too unspecific for CHD, the working group proposes an analogous algorithm for the management of PH-CHD which takes the special features of this patient group into consideration, and includes general measures, supportive therapy, targeted PAH drug therapy as well as interventional and surgical procedures. The detailed results and recommendations of the working group on PH in adults with CHD, which were last updated in the spring of 2018, are summarized in this article.